Examining the Relationship between Legal, Political Environment and Freedom of Information in Indian Print Media - Loganathan, Kannan; Kunasekaran, Puvaneswaran; S Gill, Sarjit (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to understand the relationship between legal, political environment and freedom of information in Indian print media. While previous studies only focused on the media policies and regulations, no specific research has been done to track the freedom of information in print media in India. This study traces the freedom of information in print media by exploring and analyzing the relationship between the legal environment, political environment, and freedom of information. This study employs a deductive approach on data gathered from a survey conducted on Indian journalists. Descriptive and inferential statistics were used to analyze the data. The study found that the legal and political environment are significantly related to freedom of information in print media in India.